VALIDATION OF FACT/GOG-AD SUBSCALE FOR OVARIAN CANCER-RELATED ABDOMINAL DISCOMFORT: A GYNECOLOGIC ONCOLOGY GROUP STUDY - Wenzel, Lari (2008)
OBJECTIVE: To evaluate the Functional Assessment of Cancer Therapy/Gynecologic Oncology Group-Abdominal Discomfort (FACT/GOG -AD) Subscale for assessing abdominal discomfort in patients undergoing treatment for ovarian cancer. METHODS: A four item questionnaire was developed for use in Gynecologic Oncology Group (GOG) protocol 172. It was administered to patients with advanced ovarian cancer treated on this protocol with intravenous (IV) cisplatin/paclitaxel or a combination of intravenous and intraperitoneal (IP) cisplatin/paclitaxel (IV/IP) prior to randomization, before cycle 4, 3–6 weeks after cycle 6, and 12 months after cycle 6. The subscale was evaluated in patients receiving IV/IP therapy for internal consistency, concurrent validity, sensitivity to treatment differences, and responsiveness to abdominal discomfort grading. RESULTS: Internal consistency coefficients were 0.83 and 0.87 at baseline and pre-cycle 4 assessments, respectively; the average inter-item correlation was 0.61 at the pre-cycle 4 assessment. Item correlation with other scales ranged from 0.00 – 0.44. This Subscale was able to distinguish those graded to have physician-rated abdominal pain compared to those without clinician-reported discomfort. CONCLUSION: The four item AD Subscale reliably and validly assesses ovarian cancer-specific abdominal discomfort, and captures abdominal symptom responses to IV and IV/IP cisplatin/paclitaxel treatments.